Art Education as Environmental Activism in Pre-service Teacher Education - Inwood, Hilary; Kennedy, Alysse (Journal of the Canadian Association for Curriculum Studies, 2020)
This presentation explores how art and design education can contribute to the imperative of climate change and help societies adapt to living more sustainably. Drawing on methods from arts-based research and qualitative case study, it reports on a study that investigates what can be learned from creating environmental art installations with pre-service teachers (those training to be K-12 teachers) as part of environmental art education at the Ontario Institute for Studies in Education at the University of Toronto. Data collection methods used in this study are two-fold. The arts-based research methods include journaling, photography and the creation of installations from environmental art-making experiences. Traditional qualitative methods include anonymous online surveys, semi-structured interviews and feedback forms on art workshops. Findings suggest that preservice teachers experience attitudinal and behavioural shifts towards sustainability after engaging in the processes of creating environmental art. Involvement in the workshops also provided opportunities for building community, engaging multiple domains of learning, modeling sustainable art-making practices and prompting environmental activism. Overall, connecting environmental issues with arts-based pedagogy through environmental and sustainability education (ESE) may inspire art educators to reflect on their responsibility to advance climate action and consider what role(s) they can play in environmental activism inside and outside of their educational institutions. This presentation explores how the study adds a new dimension to the current literature because of its focus on generalist pre-service teachers and pedagogical strategies that engage those with little background in art education. The results of this study inform a developing pedagogy for environmental art education in higher education settings.